Advances in regenerative medicine-based approaches for skin regeneration and rejuvenation - Dutra Alves, Nathalia Silva; Reigado, Gustavo Roncoli; Santos, Mayara; Caldeira, Izabela Daniel Sardinha; Hernandes, Henrique dos Santos; Freitas-Marchi, Bruna Leticia; Zhivov, Elina; Chambergo, Felipe Santiago; Nunes, Viviane Abreu (Frontiers in Bioengineering and Biotechnology, 2025)
Significant progress has been made in regenerative medicine for skin repair and rejuvenation. This review examines core technologies including stem cell therapy, bioengineered skin substitutes, platelet-rich plasma (PRP), exosome-based therapies, and gene editing techniques like CRISPR. These methods hold promise for treating a range of conditions, from chronic wounds and burns to age-related skin changes and genetic disorders. Challenges remain in optimizing these therapies for broader accessibility and ensuring long-term safety and efficacy.